Noise annoyance and loudness: Acoustic performance of residential buildings in tropics - Wang, C.; Si, Y.; Abdul-Rahman, H.; Wood, L.C. (SAGE Publications, 2015)
Acoustic properties of residential building are often neglected by designers, developers, contractors, and even home buyers. Noises from both the internal and external environments affect occupants' daily lives. This motivates the current study which aims to identify all types of audible noises in Malaysian residential buildings and to determine the physical and psychological impacts of noise loudness and annoyance on occupants in various types of residential buildings. A questionnaire was conducted covering 19 types of noises in residential buildings with participants assessing the loudness and annoyance level. There were 171 valid forms collected from around Malaysia for analysis from 1000 posted forms, responding rate of 17.1%. Traffic noises were deemed as the most undesired type of noise, followed by the noises from neighbors and animals. More interestingly, the annoyance experienced in relation to noise from traffic and neighbors was inter-correlated. While many animal noises such as birds chirping, rooster calls, and insect noise cause little irritation to occupants, dogs barking are significantly more annoying to the occupants. Job stress and occupants' sensitivity to noise are highly correlated with many types of noises. Generally, the influences of human-related factors are more significantly related to the housing-related factors on the perceived noise loudness and annoyance. Practical application: The result of this study could directly assist building developers and architects to enhance the acoustic (sound) properties of residential buildings. This study will guide potential property buyers how to look into the acoustic performance of the building that they are going to purchase and to stay in. All types of audible noises annoying residents in full range of residential buildings are identified and categorized in this study. The loudness and annoyance of each type of noise to resident occupants were addressed. The physical and psychological impacts of noise loudness and annoyance to the occupants in different type of residential buildings are determined, which will improve the fullness of industry standards as well regarding acoustic concern as a trend.